Why did you multiply 15 by 3?

Answers

Answer 1
Answer: To get an answer which is....45
Answer 2
Answer: I'm assuming that you want to know what we get when we multiply 15 by 3.
15 * 3 = 45.

If you are confused, then read on. :)

The * symbol means you add 15 exactly 3 times. 15+15+15=45.

Let's take 3 * 2 for example. 3 * 2 is when you add 3 for a total of 2 times. 3 + 3 = 6. You can also say that 3 * 2 is when you add 2 for a total of 3 times. 2 + 2 + 2 = 6.

So 15 * 3 = 45.
15 + 15 + 15 = 45
and
3 + 3 + 3 + 3 + 3 + 3 + 3  + 3 + 3 + 3 + 3 + 3 + 3 +3 +3 = 45.

So the answer is 45. :)

Related Questions

Mercury Orbits the sun in 87 24/25 earth days. Venus Orbits the sun in 224 7/10 Earth days, and Mars Orbits the sun in 686 49/50 days. Write each mixed number as a decimal.
What is the unit form of (2 tens 1 one) x 10
Which of the following expressions is equivalent to 6 - (-5)?a. 6 - 5 b.6 + 5 c.-6 + 5 d.-6 + (-5)
Can anyone solve this?
The expression 7 + 3x + 4 represents the perimeter of the triangle. Simplify the expression

You pay $2.40 for 3/4 pound of grapes. Your friend buys a pound of grapes at the same time and estimates that he will pay $1.80. What can you say about your friend's estimate?

Answers

Your friend's estimate is wrong because you pay $2.40 for 3/4 pound of grapes, which means 1/4 pound of grapes equals $0.80, you friend wants to any for one pound, so your friend must use 1/4 times 4 equals $0.80 times 4=$3.20 for a pound of grapes

7% of 120 (Need work shown)

Answers

1% of 120 is 1.2, so 7 *1.2 = 8.4

Also you could set up the proportion 7/100 = x/120 and solve for x.

120=100%

x= 7 %

cross-multiply

100x= 120*7

100x= 840

x= 840/100

x= 42/5

x= 8.4

Therefore 7% of 120 is 8.4


I hope that's help !


-1/3+2z=-5/6 what does z equal? -2/3x+3/7=1/2 what does x equal?

Answers

- (1)/(3) + 3z = - (5)/(6) \n \n 2z - (1)/(3) = - (5)/(6) \n \n 2z = - (5)/(6) + (1)/(3) \n \n 2z = - (1)/(2) \n \n = - (1)/(2 * 2) \n \n z = - (1)/(4) \n \n

The final result is: z = - 1/4 or z = -0.25.

----------


- (2)/(3) x + (3)/(7) = (1)/(2) \n \n - (2x)/(3) + (3)/(7) = (1)/(2) - (2x)/(3) = (1)/(2) - (3)/(7) \n \n - (2x)/(3) = (1)/(14) \n \n -2x = (1)/(14) * 3 \n \n x = (3)/(14 * -2) \n \n x = - (3)/(28) \n \n

The final result is: x = - 3/28 or x = -0.1071.
-1/3+2z=5/6 2z=5/6+1/3 z=7/6(1/2) Z=7/12 -2/3x+3/7=1/2 -2/3x=1/2-3/7 x=1/14(-3/2) X=-3/28

What is 9/12 simplified

Answers

9/12 simplified would equal 3/4 since the gcf of 9 & 12 is 3. and 9/3 is 3 and 12/3 is 4. so the answer would be 3/4
3/4 is the simplified version of 9/12

How do I solve for x

Answers

Triangles ABC and DEF are similar, which means corresponding sides are proportional to one another. Here, side AB corresponds to DE, BC to EF, and AC to DF.

We know the length of AB and AC, and we can figure out the length of BC using the Pythagorean theorem:

8^2+BC^2=17^2\implies BC=15

Sides BC and EF correspond to one another, and EF is 2 times longer than BC. This means DF is 2 times longer than 17, so that x=34.

Here is the other part sorry

Answers

Answer:

1) 32/5

2) 19/8

3) 34/7

4) 25/3

How to do this

You take the denominator (the number on the bottom), multiply it by the whole number (like in 1, 5*6=30) then add the numerator (the top number) (so 30+2) then add on top of the denominator before you changed anything (32/5)